Effects of price information on physician decision making - Gan, Hui Ching (2008)
This study investigates whether the provision of price information would significantly affect physicians' decision-making process.In particular, we look at the effects of providing price information for four cost drivers of the haemorrhoids condition to physicians treating haemorrhoids patients.We then propose to profile and make public information on the cost drivers in which price information has a significant impact on physicians' decisions.